The vulnerabilities of computerized physician order entry systems: a qualitative study. (13th November 2015) - Slight, Sarah P; Eguale, Tewodros; Amato, Mary G; Seger, Andrew C; Whitney, Diana L; Bates, David W; Schiff, Gordon D
Abstract: Objective To test the vulnerabilities of a wide range of computerized physician order entry (CPOE) systems to different types of medication errors, and develop a more comprehensive qualitative understanding of how their design could be improved. Materials and Methods The authors reviewed a random sample of 63 040 medication error reports from the US Pharmacopeia (USP) MEDMARX reporting system where CPOE systems were considered a "contributing factor" to errors and flagged test scenarios that could be tested in current CPOE systems. Testers entered these orders in 13 commercial and homegrown CPOE systems across 16 different sites in the United States and Canada, using both usual practice and where-needed workarounds. Overarching themes relevant to interface design and usability/workflow issues were identified. Results CPOE systems often failed to detect and prevent important medication errors. Generation of electronic alert warnings varied widely between systems, and depended on a number of factors, including how the order information was entered. Alerts were often confusing, with unrelated warnings appearing on the same screen as those more relevant to the current erroneous entry. Dangerous drug-drug interaction warnings were displayed only after the order was placed rather than at the time of ordering. Testers illustrated various workarounds that allowed them to enter these erroneous orders. Discussion and Conclusion The authors found high variability in ordering approaches between different CPOE systems, with major deficiencies identified in some systems. It is important that developers reflect on these findings and build in safeguards to ensure safer prescribing for patients.